Vozes das catástrofes: teias de resistência Xikrin entre Belo Monte e a COVID-19 - Foltram, Rochelle (Universidade Federal de São Carlos, 2024)
In the depths of the Trincheira Bacajá Indigenous Land, along the banks of the Bacajá River, an unrelenting saga of resistance unfolds. This thesis paints the picture of the Mebêngôkré-Xikrin's tireless struggle, touched by the waters of the river that now resonate with the roar of Belo Monte. Confronted by socio-environmental projects devised in response to the imposing Environmental Basic Plan of Norte Energia, the Xikrin intertwine their history with threads of combat and resilience. Each project emerges as a manifesto, a cry of resistance in the face of the challenges imposed by 35 years of forced coexistence with the hydroelectric plant and the threat of ethnocide. In the fabric of this narrative, the pandemic years unfold as an additional chapter in Xikrin life. COVID-19, like a relentless tempest, intertwines with resistance, challenging the Xikrin to confront not only the invasion of their waters but also the fleeting shadows of a global disease. This thesis is a chant, an echo of Xikrin voices that resonate beyond the waters, beyond the imposed challenges, an ode to the resistance that shapes itself with each dawn, bringing the promise of a tomorrow where indigenous culture and life flourish amid tireless struggle.
Voices of catastrophes: Xikrin resistance networks between Belo Monte and COVID-19
Keywords: Mebêngôkré-Xikrin; Resistência; Belo Monte; COVID-19; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA